Two new species of Encarsia Förster (Hymenoptera, Aphelinidae) and first description of the male E. plana Viggiani & Ren from China - Wang, Zhu-Hong (Zootaxa, 2014)
Two new species of Encarsia Förster (Hymenoptera: Aphelinidae) are described from China, Encarsia floralis Wang, Huang & Polaszek, sp. nov. and Encarsia maculiformis Wang, Huang & Polaszek, sp. nov., and the male of Encarsia plana Viggiani & Ren (1987) is newly described.